Molecular Characterization and Antimicrobial Resistance of Escherichia coli Isolated from Mastitis in Dairy Animals - Bothikar, Akash A.; Mhase, Prashant P.; Manmod, Pranita G.; Tumlam, Uma M.; Pawar, Prashant D.; Jadhav, Sameer N. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study investigated the prevalence of bovine mastitis and antimicrobial resistance patterns of Escherichia coli isolates from dairy animals in Western Maharashtra. A total of 400 lactating cows were screened for mastitis using the California Mastitis Test (CMT) and cultural examination. Of these, 210 (52.50%) animals were confirmed positive, comprising 19.52% (n=41) clinical and 80.47% (n=169) subclinical mastitis cases. Bacteriological analysis revealed Staphylococcus spp. as the predominant pathogen (40.95%), followed by other Gram-positive bacteria, while E. coli accounted for 22.85% (48/210) of the isolates. Antimicrobial susceptibility testing of all bacterial isolates demonstrated highest sensitivity to Amikacin (88.09%) and Ciprofloxacin (82.38%), whereas marked resistance was observed against Gentamicin (69.52%) and Ampicillin-Sulbactam (71.42%). Among E. coli isolates, high susceptibility was recorded for Amikacin (89.58%) and Cefotaxime-Clavulanic acid (83.33%), while resistance to Gentamicin was observed in 68.75% of isolates. MIC50 findings corroborated the disc diffusion results. Molecular confirmation using 16S rRNA PCR yielded a specific 401 bp amplicon. Resistance gene profiling revealed a high prevalence of blaTEM (70.83%), tetA (64.58%), aac(3)-IV (62.50%), qnrA (52.08%), and blaSHV (6.25%). Multidrug resistance was detected in 53.30% of all isolates and 22.91% of E. coli isolates, with common gene combinations including blaTEM+tetA (45.83%) and blaTEM+qnrA (35.41%). The study highlights the alarming emergence of multidrug-resistant E. coli in bovine mastitis and underscores the need for routine antimicrobial surveillance and rational antibiotic use in dairy farms.
Keywords: Antimicrobial resistance; Bovine mastitis; Escherichia coli; MDR; Resistance genes